2018
DOI: 10.1002/ccd.27569
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical and quality of life outcomes after stenting of femoropopliteal artery stenosis: 3‐year results from the STROLL study

Abstract: In patients undergoing revascularization for moderately complex SFA disease, use of the self-expanding S.M.A.R.T® stent was associated with a high rate of target vessel patency through 3 years and led to substantial and sustained health status benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…6,26,27,31 All-cause mortality from the DCB group in IN.PACT SFA Japan was also consistent with studies of other endovascular modalities that have reported outcomes at 36 months, including MAJESTIC (DES, 3.6%), RESILIENT (BMS, 10.0%), DURABILITY II (BMS, 10.1%), and STROLL (BMS, 10.1%). [32][33][34][35] The rate of thrombosis after DCB angioplasty in IN.PACT SFA Japan, while low (1.5%), was consistent with what has been reported for DCBs at 36 months (IN.PACT SFA 2.0%, IN.PACT Global 5.6%, not reported in REAL-PTX, ILLUMENATE EU, or ILLUMENATE US). 6,26,27,31 Efficacy outcomes from IN.PACT SFA Japan were consistent with other DCB studies at 36 months (Table 6).…”
Section: Discussionsupporting
confidence: 86%
“…6,26,27,31 All-cause mortality from the DCB group in IN.PACT SFA Japan was also consistent with studies of other endovascular modalities that have reported outcomes at 36 months, including MAJESTIC (DES, 3.6%), RESILIENT (BMS, 10.0%), DURABILITY II (BMS, 10.1%), and STROLL (BMS, 10.1%). [32][33][34][35] The rate of thrombosis after DCB angioplasty in IN.PACT SFA Japan, while low (1.5%), was consistent with what has been reported for DCBs at 36 months (IN.PACT SFA 2.0%, IN.PACT Global 5.6%, not reported in REAL-PTX, ILLUMENATE EU, or ILLUMENATE US). 6,26,27,31 Efficacy outcomes from IN.PACT SFA Japan were consistent with other DCB studies at 36 months (Table 6).…”
Section: Discussionsupporting
confidence: 86%
“…The CEC-adjudicated all-cause mortality of 11.6% in this study is consistent with the range of 3-year rates (3.9% to 12.5%) in other contemporary studies of both drug-coated and uncoated devices. 30 34 Causes of death were varied and congruent with the age and the high level of comorbidities in this patient population. A study-level meta-analysis 35 reported an association between paclitaxel-coated devices (DCB and DES) and mortality.…”
Section: Discussionmentioning
confidence: 88%
“…The IN.PACT Global study stands up to RCTs that studied BMS. The RESILIENT, 29 STROLL, 30 DURABILITY II, 31 and SUPERB 32 trials (mean lesion lengths of ~7–9 cm), which evaluated BMS at 36 months had estimated freedom from TLR rates of 75.5%, 75.8%, 69.7%, and 82%, respectively. The MAJESTIC trial 24 (Eluvia DES) had a promising 85.3% freedom from CD-TLR estimate at 36 months.…”
Section: Putting the Study To The Testmentioning
confidence: 99%